Probable Value for the Next Sunspot Minimum - Virginia Mabel Silbergleit (Advances in Astronomy)
Gumbel’s first distribution is applied to smoothed monthly mean sunspot numbers for solar cycles 10 to 24. According to that, the next minimum for solar cycle 24-25 transition would be the deepest solar minimum of the last 150 years. This study provides an additional insight about changes in the Sun which are currently happening.